Визначення можливостей отримання структурованого робочого шару абразивного інструменту з надтвердих матеріалів - Лавріненко, В.И.; Пасічний, О.О.; Ситник, Б.В.; Ткач, В.М.; Лєщук, І.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The problem on importance of the count of structural orientation in a working layer of abrasive wheels from SHM surveyed. Technological aspects with reference to requirements of a molding and sintering of a working layer of circles are shown at which it is possible to implement requirements of change of structural orientation of such layer. Features of a grinding composite with diamond around surveyed.